Metal concentrations in sediment and fish of Lake Victoria near and away from catchments with gold mining acctivities - Machiwa, JF (Tanzania Journal of Science, 2021)
Concentrations of metals in sediment and fish as well as organic matter contents of sediment from Lake Victoria were investigated. The objective of the study was to compare levels of metals in sediment and fish from areas of the lake that are within and outside catchments with gold mining activities. The results showed that the concentration of As was less than 6 mg g-1 dw and Cd was below 1.9 mg g-1 dw in sediment samples. Lead, zinc and copper concentrations were highest (58.1±17.6 mg g-1 dw, 101.9±20.6 mg g-1 dw and 32.6±2.8 mg g-1 dw respectively) in sediment samples that were collected in the lake adjacent to the Mirongo River mouth in urban Mwanza. The results showed no correlation between levels of heavy metals and the organic matter content of the sediment. Metal concentrations in fish muscles were generally low. For instance, in Lates niloticus the highest concentrations of cadmium, lead and copper (4.67±1.87 ng g-1 ww, 0.13±0.04 mg g-1 ww, 0.7±0.2 mg g-1 ww respectively) were found in fish caught adjacent to the Mirongo River mouth. Apparently, zinc concentrations in Lates niloticus were highest (8.8±4.1 mg g-1 ww) in specimens from Mara Bay. Concentrations of heavy metals in sediments and fish from areas within and away from catchments with gold mining activities were not statistically different (P > 0.05). It is concluded that at present mining in the lake basin has no significant impact on lacustrine environment.